2014
DOI: 10.1186/1471-2156-15-60
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTL conferring resistance in maize to gray leaf spot disease caused by Cercospora zeina

Abstract: BackgroundGray leaf spot (GLS) is a globally important foliar disease of maize. Cercospora zeina, one of the two fungal species that cause the disease, is prevalent in southern Africa, China, Brazil and the eastern corn belt of the USA. Identification of QTL for GLS resistance in subtropical germplasm is important to support breeding programmes in developing countries where C. zeina limits production of this staple food crop.ResultsA maize RIL population (F7:S6) from a cross between CML444 and SC Malawi was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 40 publications
9
72
0
Order By: Relevance
“…If this hypothesis is true, related studies on maize disease resistance should note biological roles for QTLs that include ZmTps21. Supportively, independent disease-related QTLs have been detected in broad regions spanning bin 9.05 (Baumgarten et al, 2007;Berger et al, 2014). More specifically, ZmTps21 (GRMZM2G011151) has been identified as uniquely present in transcriptome analyses of resistant inbred lines associated with enhanced antifungal defenses (Lanubile et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…If this hypothesis is true, related studies on maize disease resistance should note biological roles for QTLs that include ZmTps21. Supportively, independent disease-related QTLs have been detected in broad regions spanning bin 9.05 (Baumgarten et al, 2007;Berger et al, 2014). More specifically, ZmTps21 (GRMZM2G011151) has been identified as uniquely present in transcriptome analyses of resistant inbred lines associated with enhanced antifungal defenses (Lanubile et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Resistance of maize germplasm to GLS is quantitative in nature with many QTL identified in different maize growing countries, although very few studies have defined the causal species (Berger et al 2014). The pathosystem is not characterized by pathogen races that are recognised by cognate resistance genes (Balint-Kurti et al 2008), however the high diversity and evidence for sexual recombination reported in this study reveal a potential for differences in virulence between C. zeina isolates.…”
Section: Population Differentiation Was Low Within Thementioning
confidence: 99%
“…Widespread adoption of conservation tillage has allowed many fungal foliar pathogens to over-winter on maize debris, thus increasing the inoculum pressure in subsequent growing seasons (Ward et al 1999). Maize foliar disease resistance breeding is ongoing (Berger et al 2014), and this is particularly important for small-holder farmers in developing countries who currently have limited access to chemical control.…”
Section: Introductionmentioning
confidence: 99%
“…Berger et al. () used recombinant inbred line (RIL) populations constructed from CML444 × SC Malawi and detected seven QTLs that explained more than 11% of the phenotypic variation in 11 environments on chromosomes 1, 4, 7, 9, and 10. Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…() used meta‐analysis methods to integrate the QTL mapping results of five GLS resistance studies and identified 26 “real” QTLs and seven hotspots in bins 1.06, 2.06, 3.04, 4.06, 4.08, 5.03, and 8.06. In addition to directly locating maize GLS resistance QTLs, attempts were made to locate QTLs related to the control of flowering time, and a close connection was detected between the two traits (Berger et al., ; Liu et al., ).…”
Section: Introductionmentioning
confidence: 99%